Structure and dynamics of Aldegondabreen, Spitsbergen, according to repeated GPR surveys in 1999, 2018 and 2019 - A. L. Borisik; A. L. Novikov; A. F. Glazovsky; I. I. Lavrentiev; S. R. Verkulich (Ice and Snow, 2021)
Over the last decades, glaciers on Svalbard were shrinking in response to the current climate change. Most of them decreased in size, area, and surface height with a stable negative or even accelerated changes in the mass balance. Many of them belong to the polythermal type, and as they shrink, their thermal regime can also change significantly depending on the climate and local parameters such as the ice facies distribution, the firn thickness, and others that affect the hydrology and movement of glaciers. Data from repeated GPR surveys in 1999 and 2018–2019 were used to identify changes in the thermal regime of the polythermal Aldegondabreen, Svalbard. The glacier has undergone a significant reduction of its temperate ice core, as a consequence of steadily negative mass balance, decreasing thickness, and the tongue retreat. The results show that over a 19‑year period, the total area of the glacier has decreased by 23.1% (from 6.94 to 5.34 km2), and the total volume of ice – by 36.4% (from 0.437 to 0.278 km3). At the same time, the area of its temperate core has decreased by 32.7% (from 1.196 to 0.804 km2), and the core volume – by 42.5% (from 0.035 to 0.02 km3). In this way, the relative rates of internal glacier changes associated with the warm core exceeded the external changes of the entire glacier. The share of temperate ice in the total volume of the glacier ice decreased from 8% to 7%. The glacier shrinking in response to rise of the air temperature was accompanied by its gradual internal «cooling». In the near future, this can result in a rapid transition of the glacier from a polythermal type into a cold one. Regular repeated geophysical surveys of the internal structure of the Svalbard polythermal glaciers can become an important element in the system of long-term monitoring of changes in climate and the natural environment of the archipelago, along with already existing observations of other sensitive natural indicators such as the size and mass balance.